Effects of pituitary adenylate cyclase activating peptide (PACAP) and related peptides on human retinoblastoma Y79 cells - Honório, José Miguel Santos da Fonseca Beja (2017)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2014